OP0093 Comparison of CD34-Selected and Unmanipulated Autologous Hematopoietic Stem Cell Transplantation for Systemic Sclerosis: Four-Year Follow-Up Results. (10th June 2014) - Tsukamoto, H.; Ayano, M.; Miyamoto, T.; Niiro, H.; Arinobu, Y.; Akahoshi, M.; Akashi, K.
Abstract : Background: The superior efficacy of autologous hematopoietic stem cell transplantation (auto-HSCT) versus intravenous pulses cyclophosphamide was demonstrated in a randomized phase II trial in 19 severe systemic sclerosis (SSc) patients and a large randomized phase III trial in 156 patients. However, the usefulness of CD34-selection in auto-HSCT for SSc has not been investigated. Objectives: The aim of this study is to compare the safety and the efficacy of CD34-selected auto-HSCT with those of unmanipulated auto-HSCT for severe SSc during a four-year follow-up period. Methods: Nineteen patients (4 male and 15 female) with severe SSc were enrolled. Peripheral blood stem cells (PBSCs) were mobilized with cyclophosphamide (CY, 4 g/m 2 ) and G-CSF. After collecting PBSC more than 2×10 6 CD34+ cells/kg by apheresis, CD34+ cells were immunologically selected in 11 patients. All of the patients were treated with high-dose CY (200 mg/kg) and received CD34-selected (n=11; group A) or unmanipulated (n=8; a group B) auto-HSCT. Immune reconstitution was evaluated serially by analyzing lymphocyte subpopulations for 48 months after HSCT. Results: The age of the patients was 52.3±7.5 years in group A and 55.1±5.5 years in group B. The modified Rodnan's skin score was 21.5±14.0 in group A and 22.9±9.0 in group B. Numbers of the infused CD34+ and CD3+ cells were 4.7±2.6×10 6 and 0.011±0.012×10 6 /kg, respectively, in group A and 7.6±10.7×10 6 and 45.6±28.1×10 6 /kg, respectively, in group B. The time to engraftment of neutrophil and platelet was not different between two groups. There was no treatment-related mortality in both groups. As toxicity, 2, 5 and 6 out of 11 patients had adenoviral hemorrhagic cystitis, herpes zoster and cytomegaloviral antigenemia, respectively, in the group A, on the other hand, no patients had adenoviral hemorrhagic cystitis, herpes zoster and only 2 out of 8 patients had cytomegaloviral antigenemia, respectively, in group B. All of the patients in both groups had marked improvement of skin sclerosis within 3 months and the improvement was sustained for 48 months after auto-HSCT. Surprisingly, the reduction of the skin scores was significantly greater at 1 and 12-48 months after auto-HSCT in group A than in group B. About the effect on interstitial pneumonia, %VC increased continuously until 48 months after auto-HSCT in group A, on the other hand, it once increased but decreased after 12 months in group B. The recovery of lymphocyte subpopulations after auto-HSCT was not significantly different between two groups. Conclusions: CD34-selected auto-HSCT had greater effects but more susceptiblity to viral infections than unmanipulated auto-HSCT. References: Tsukamoto H, Nagafuji K, Horiuchi T, et al. A Phase I-II Trial of Autologous Peripheral Blood Stem Cell Transplantation in the Treatment of Refractory Autoimmune Disease. Ann Rheum Dis. 65: 508-14, 2006. Tsukamoto H, Nagafuji K, Horiuchi T, et al. Analysis of immune reconstitution after autologous CD34+ stem/progenitor cell transplantation for systemic sclerosis: predominant reconstitution of Th1 CD4+ T cells. Rheumatology (Oxford) 50: 944-52, 2011. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3166